Exploiting Narrative Literary Texts through Questions in Reading Comprehension - Davy Budiono (Magister Scientiae, 2011)
Teacher’s creativity is needed in developing the teaching materials for reading comprehension. This assumption is concluded based on a study that revealed that most students and teacher candidates of English are having serious in both constructing and providing answers to inferential and analytical questions. This article discusses the selection and the exploitation of suitable narrative literary materials for teaching reading comprehension. This paper begins with the discussion of the advantages of using narrative literary texts in teaching reading comprehension. It is followed by a short description on how literary texts can be exploited by constructing closed and open questions based on Barrett’s taxonomy of reading comprehension levels. However, as teachers of English it is essential that the communicative aspects of language learning should be kept in focus as individual answers may arise.